2017
DOI: 10.1080/10410236.2017.1384353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Message Framing on Influenza Vaccination: Understanding the Role of Risk Disclosure, Perceived Vaccine Efficacy, and Felt Ambivalence

Abstract: The current study examined the effects of framing in promotional health messages on intention to vaccinate against seasonal influenza virus. The findings of an experimental study (N = 86) indicated that exposure to both benefits and side effects of vaccination (gain-framed with risk disclosure message) led to lower intention to receive the flu vaccine. This relationship was mediated by both perceived vaccine efficacy and felt ambivalence in a serial order, revealing the underlying psychological mechanisms impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 61 publications
6
51
0
Order By: Relevance
“…Findings warrant promotional health messages framing a high risk of illness, as this has been found useful in influencing vaccine-related behavior. 18 Males were the only demographic predictor of having a definite intention of COVID-19 vaccination, which implies the need for gender-based intervention. It is important to note that in this study the price of the COVID-19 vaccine is not a significant predictor of vaccination intent.…”
Section: Discussionmentioning
confidence: 98%
“…Findings warrant promotional health messages framing a high risk of illness, as this has been found useful in influencing vaccine-related behavior. 18 Males were the only demographic predictor of having a definite intention of COVID-19 vaccination, which implies the need for gender-based intervention. It is important to note that in this study the price of the COVID-19 vaccine is not a significant predictor of vaccination intent.…”
Section: Discussionmentioning
confidence: 98%
“…Perceived vaccine efficacy is the belief that a vaccine will reduce the likelihood of infection or disease that can occur without the vaccine (Nan et al, 2012). The importance of vaccine efficacy in vaccine uptake is evident in several studies (e.g., Kim et al, 2017;Teo et al, 2019). A study focusing on message framing found that perceived vaccine efficacy mediated the relationship between message framing and influenza vaccination intention (Kim et al, 2017).…”
Section: Perceived Vaccine Efficacy As a Mediatormentioning
confidence: 99%
“…The importance of vaccine efficacy in vaccine uptake is evident in several studies (e.g., Kim et al, 2017;Teo et al, 2019). A study focusing on message framing found that perceived vaccine efficacy mediated the relationship between message framing and influenza vaccination intention (Kim et al, 2017). Another qualitative study in older adults found that trust in vaccine efficacy was a strong motivator of vaccine uptake (Teo et al, 2019).…”
Section: Perceived Vaccine Efficacy As a Mediatormentioning
confidence: 99%
“…Because of its significance to public health, there have been numerous studies of the factors that cause “vaccine hesitancy” (Hornsey et al, 2018; Puri et al, 2020; Thunström et al, 2020). Most of the studies have focused on decision-making in the context of parents vaccinating their children, the acceptance of the HPV vaccine, or decision-making with respect to the flu vaccine (Brewer et al, 2007; Callaghan et al, 2020; Dubé et al, 2013; Kim et al, 2019; Nan et al, 2015; Smith et al, 2017).…”
Section: Framing Effects and Vaccination Beliefsmentioning
confidence: 99%